Evaluation proteolytic and lipolytic activity of strains for the treatment of tannery effluents - Alcarraz Curi, Mario (2014)
The investigated effluents have a high BOD (Biochemical Oxygen Demand) represented mainly by proteins and lipids ; which motivated the search for microorganisms with proteolytic and lipolytic capabilities for a potential biological treatment of these effluents. 39 strains were selected for testing, of these, 41% were positive for proteolytic activity, lipolytic activity to 51% and 38% for both activities; also grew 100% in pH 9 and 10, 79.5% in pH 11 and 54% at pH 12 is worth noting that of all strains tested two (N3D and N4E) presented the best proteolytic and lipolytic activities respectively. We conclude that in tannery effluents are microorganisms with high enzymatic potential of bioconversion.